The Role of Satisfaction as Mediator of the Effect of Service Quality on Customer Loyalty - Gregorius Titan R.D; I Gst Agung Ketut Gede Suasana (PT FORMOSA CENDEKIA GLOBAL, 2023)
The shifting of customer behavior from conventional to digital is driving Bukalapak to invent a new solution to ease the online transaction. Year after year, Bukalapak keep losing its platform visitor. The objective of this study is to elucidate the impact of satisfaction with the quality of mediation services on customer loyalty within the context of Bukalapak. The research was carried out in Bogor Regency and involved a sample of 104 participants. The selection of the total sample was determined using a non-probability sampling technique. The distribution of survey questions was conducted online through the Google Form platform. The methods employed in this research involve trajectory analysis and the utilization of the Sobel test. The findings of the study reveal that there is a noteworthy positive influence of service quality on customer loyalty. Moreover, the study establishes a substantial positive connection between service quality and satisfaction, as well as between satisfaction and customer loyalty. Additionally, satisfaction is demonstrated to have a considerable positive effect on service efficiency